Judicial Control on “Internal Corporal Acts”: Case of the Right Action of Inconstitutionality 6524 In the Light of the Exception of the Political Nature of Rui Barbosa - Martonio MONT´ALVERNE BARRETO LIMA; PINHEIRO LEITÃO, Francisco Thiago (Revista Jurídica Portucalense, 2024)
The article aims to carry out an analysis of the judgment of Direct Action of Unconstitutionality 6,524 by the Supreme Federal Court in relation to the thesis of the exception of the political nature of the cause defended by Rui Barbosa, in order to identify the relevance of the respective teachings. Therefore, the analysis will aim to compare the judgment of Direct Action of Unconstitutionality 6,524 and Rui Barbosa's lessons on the constitutional exception. This is bibliographic and documentary research. The hypothesis is that the control of purely political acts is possible, as long as they keep projection in the text of the Constitution. The conclusion of the research was that the judgment of ADI 6,524 is in line with the thesis of political nature and its consequences, especially under the political role played by the Supreme Court.